Efforts to Improve Quranic Reading and Writing Skills Through Local Content Learning for Quranic Reading and Writing (BTQ) at Ad-Dzikir Pragaan Elementary School, Sumenep, 2023 - Hanifah Hanifah; Fathorrahman Fathorrahman (Tilawah: Journal of Al-Qur'an Studies, 2026)
As is currently the case, the majority of children cannot read the Quran properly. Even young and emerging adults still read the Quran without paying attention to tajweed and the correct pronunciation of the letters. This is crucial for maintaining accuracy and fluency in reading the Quran, as even a single error in the rules can alter its meaning and lead to sin. The problem raised in this study is how to improve the ability to read and write the Qur'an through local content learning to Read and Write the Qur'an at Ad-Dzikir Pragaan Elementary School, how to implement local content learning to read and write the Qur'an for students and what are the supporting and inhibiting factors in improving the ability to read and write the Qur'an for students at Ad-Dzikir Pragaan Elementary School. To find out more about this research, the researcher used a qualitative research method with a descriptive qualitative type. Data collection in this study used 3 ways, namely interviews, observation and documentation. The results of this study are that the learning implemented at Ad-Dzikir Pragaan Elementary School has been implemented since the beginning of this school, and there are several efforts made by teachers to improve students' ability to read and write the Qur'an. Namely; Accustoming students to reading the Quran while simultaneously researching the rules of recitation, encouraging students to check their writing, evaluating their Quran reading through memorization, encouraging students to write the Quran according to the letter placement, and emphasizing the memorization of the Quranic chapters (suras) and requiring memorization of the 30th chapter (juz') for final year students (grade 6). Of course, this approach has both supporting and inhibiting factors.